The motives for issuing exchangeable bonds in the privatization of state-owned enterprises - Damian Kaźmierczak (Comparative Economic Research. Central and Eastern Europe, 2023)
Using a unique sample of exchangeable bond issues carried out in seven countries since the 2000s, this paper investigates the role of hybrid debt in the privatization of state-owned enterprises (SOEs) via government-controlled investment vehicles. This research shows that so far, sixteen series of exchangeable bonds amounting to approx. USD 25 billion were issued to privatize ten SOEs in the telecommunication, energy, basic materials, industrials, healthcare, and utilities sectors in Europe and Asia. Moreover, in some cases, the privatization of SOEs by means of exchangeables can prove to be a more favorable alternative to traditional methods of selling shares directly on the capital market, for example, via IPOs or SPOs (during periods of deep undervaluation of privatized companies or of high stock market volatility). First, shares can be sold at a later date and at a higher price. Second, the impact on the stock market price of an SOE may be less disruptive to shareholders. Third, the entire privatization process tends to be more flexible for issuers in that they can perceive exchangeables as a source of relatively cheap, long-term external capital while keeping control over the privatized company until the potential conversion of debt by bondholders.
Keywords: G32; G34; G38; L33; 330; state-owned enterprises; privatization; equity-linked securities; exchangeable bonds